Secuelas respiratorias en pacientes con enfermedad pulmonar obstructiva crónica posterior a infección por covid-19 - Acosta Freire, Dennis Omar (2023)
ABSTRACT: Chronic obstructive pulmonary disease is the respiratory condition that most frequently occurs in adults, especially in older adults. It occupies a privileged place and is considered one of the leading causes of morbidity and mortality in this population group. The involvement of COVID-19 can condition sequelae that generate greater respiratory involvement in patients with this disease, which would condition an unfavorable prognosis in all senses. This research aimed to conduct a bibliographic review to obtain updated information on the sequelae of COVID-19 in patients with chronic obstructive pulmonary disease. For this, a basic, descriptive, and cross-sectional investigation was carried out consisting of a bibliographic review of documents published in the last five years. A total of 70 documents were identified, of which 46 were used in the study. The information was obtained from regional (Latindex, Lilacs, Scielo, and Redalyc) and high-impact databases (Scopus, Medline, PubMed, and Ice Web of Science). The main results include the description of the clinical and etiopathogenic characteristics of the disease, the etiopathogenic mechanisms of COVID-19 that affect patients with respiratory disease, and the sequelae that this can generate. A proposed follow-up scheme includes clinical, laboratory, and imaging elements. Keywords: Coronaviruses; Covid-19; Chronic obstructive pulmonary disease; Respiratory sequelae; Post Covid-19 syndrome.